Sustained censorship in KZ (2022-01) (Kazakhstan) - Voidly (Voidly Global Censorship Index, 2022)
WARNING severity censorship detected in Kazakhstan. Data sourced from OONI.
Censorship Incident ID: KZ-2022-0002. Severity: warning. Confidence: 75%